NONLINEAR OPTICS' EFFECT ON ADVANCED IMAGING TECHNOLOGIES - Ahmed Mohammad Ali Eshwi, ⁠Fahad Bader Abdulrahman Alharbi, ⁠Samer Mohammed Abdulhakeem Alshobaiki, ⁠Abdualrhman Mohmmad Shabiah Adam, Hamad Mohamed Abdulla Aldosery, Hassan Hamzah Hassan Adawi,⁠,; Rami Salem Ghannam Alsaidi,Fayiz Mathkar Alzarraqi Alotaibi ,Lamia Saleh Thaher Alasheash, Maha Hassan Abdullah Alzahrani, Ghezlan Fahad Saeed Aldossary, Rashad Mohammed Hassan Alnami , (Chelonian Research Foundation, 2022)
Nonlinear optics has significantly impacted innovative imaging technologies by enabling various operations such as spectrum transformation, nonlinear absorption, nonlinear dispersion, as well as phase and amplitude modulation. Optical materials including glasses, crystals, nanomaterials, and polycrystalline substances are essential in nonlinear optical processes. Cubic nonlinear optical processes do not need noncentrosymmetric structures, although second-order nonlinear optical effects must. Anisotropic crystals like KDP, LiNbO3, BBO, and KTP are often used for second-order nonlinear optical applications, whereas glasses are suitable for third-order nonlinear optical applications. Polycrystalline compounds, often considered inappropriate for optics because of their strong light scattering, are now being considered as potential nonlinear optical pigments. Nanocrystals, such as upconverting nanoparticles and quantum dots, exhibit altered optical characteristics compared to bulk media and have promise for nonlinear optical uses. Microcrystalline materials, including metal-organic complexes and cooperation polymers, have been studied for their potential as nonlinear optical media. NLO pigments, compounds with nonlinear absorption and extra optical properties, do not need great optical transparency. Novel nonlinear optical (NLO) materials have been used in laser advancements for nonlinear microscopy, optical power restriction, and saturation absorbers. Semiconductor quantum dots are being considered as effective replacements for organic dyes in nonlinear microscopy for luminous marking. Optical power restriction may be achieved by two-photon processes that occur directly or through two-step mechanisms in materials that absorb a third photon after absorbing two photons. Evaluating the nonlinear absorption capabilities of new compounds often depends on their effectiveness as saturable absorbers in laser systems. Understanding the temporal response of saturable absorbers is crucial for laser mode-locking, since they may be categorized as either fast or slow. The recovery time of saturable absorbers determines the duration of mode-locked pulses. Femtosecond lasers and time-resolved pump-probe methods may be used to determine the temporal properties of saturable absorbers. This article explores the impact of nonlinear optics on advanced imaging technologies, focusing on the importance of different optical materials and their use in nonlinear optical processes. Advancements in NLO materials provide potential for improved optical features and imaging technologies. Keywords: Optical power limitation, nonlinear microscopy, saturable absorbers, mode-locking, microcrystalline substances.